Digitalization in the agri-food industry: the relationship between technology and sustainable development. Issue 8 (13th July 2020) - Carmela Annosi, Maria; Brunetta, Federica; Capo, Francesca; Heideveld, Laurens
Abstract : Purpose: Digitalization is becoming the subject of considerable interest in the literature. This is in view of its relevance in addressing social problems and contributing to the development of communities and societies. In the agri-food-industry, digitalization is also expected to contribute significantly to solve several challenges the sector is facing at this moment, such as the increasing food demand and resource use. However, the effects of advanced technologies are less a function of the technologies themselves than of how they are used by people. The study analyses the dominant challenges faced by firms in the agri-food industry in the usage and adoption of digital technology. Also, they show how these challenges impact on the sustainable development of digital technology for firms in the industry and provide avenues for future research. Design/methodology/approach: The authors propose a structured literature review aiming to investigate the following research question: what are the main challenges faced by firms within the agri-food industry in the adoption of smart technologies? Findings: Results illustrate the dominant challenges faced by firms in the agri-food industry in the usage and adoption of digital technology. Also, they show how these challenges impact on the sustainable development of digital technology for firms in the industry and provide avenues for future research. Originality/value: So far, in the context of digitalization in the agri-food industry, various researchers have analysed different kinds of challenges to the adoption of smart technologies. This work reviews these contributions to create a clear reference framework of the challenges faced by agri-food firms while providing future avenues of research and implications at a policymaking, economic-managerial and socio-environmental level.